Influência estrutural na configuração geomorfológica do setor sudeste da Paraíba e nordeste de Pernambuco - Lima, Vinícius Ferreira de (2021)
The research presented, seeks to bring unpublisheded contributions to the geomorphology studies from the influence of lithological structures and tectonic activity in the elaboration of the relief and the drainage network, applying geomorphological mapping as a synthesis tool for relief representation. In this sense, the main goal of this thesis is to understand how the geomorphological model was elaborated, with a tectonic structural focus, in the Southeast sector of the state of Paraíba and Northeast sector of the state of Pernambuco, considering as an analytical background the existing interrelations between the geology, the relief and the hydrography of the area, without disregarding, however, the significant human activities in the geomorphological evolution of the area. We sought to point out neotectonics evidence in the study area, through morphotectonic and morphometric analysis applied in basins and sub-basins in the area. The elaboration of the geomorphological chart was based on the methodology proposed by Ross (1992), with adaptations, which are based on the taxonomic units of the relief. For the morphotectonics analysis, in addition to the morphological investigation, morphometric indices were applied, in order to investigate anomalies in the drainage network patterns, related to recent tectonics. The Declivity / Extension Ratio (RDE), Bottom / Valley Height Ratio (VF) and Asymmetry Factor (AF) indices were used in this study, with the intention of indicating possible changes in the course of rivers over geological time, to ascertain the carving of the valleys and the hilldown slopes and pointing out signs of asymmetry related to the slope of the terrain and/or tilting. The results enabled it possible to recognize anomalous patterns in the drainage network, both in qualitative and quantitative aspects, and in the forms of relief, which probably find direct correspondence with recent regional tectonic events, which covers the entire eastern border of Northeast Brazil. The area is inserted between the crystalline basement of the Precambrian and the Paraíba Sedimentary Basin. For the morphostructural and morphotectonic analysis, maps were elaborated: hypsometric, clinographic and geomorphological, in addition to substantial adjustments in the geological map to adapt the scale used in the research. Within the geomorphology of the region, several deformation patterns were presented that add strong indicators of the lithological structures performance and tectonic activities in the development of the relief and drainage network, both in the areas of crystalline lithology and sedimentary lithology, for example: succession of grabs and horsts; structural domes that can be associated with tectonic inversion structures; alignments relief and drainage network; different altitudes in tabular tops interfluves that confine the regional river valleys; rectilinear drainage channels that present strong inflections; occurrence of abrupt unevenness in river channels (knickpoints), among others. The elaboration of the geomorphological map, reflects all the relief in a scale of unpublished detail for this area, resulting in the presentation of the six taxons proposed in the methodology of Ross (1992). The obtained results prove that cannot be denied.the influence of post-Myocene tectonics in the configuration of the relief in the adjacencies of a Passive Continental Margin.